1985
DOI: 10.1128/jcm.22.2.176-181.1985
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the automicrobic system, acridine orange-stained smears, and gram-stained smears in detecting bacteriuria

Abstract: We compared the accuracy of the Gram-stained smear, the acridine orange-stained smear, and the AutoMicrobic system (AMS; Vitek Systems, Inc., Hazelwood, Mo.) in screening for bacteriuria, as detected by conventional cultures. For 1,024 clinical specimens, results with the acridine orange-stained smear and the Gram-stained smear were very similar. When read for the presence of one or more microorganisms or leukocytes per 20 oil immersion fields, both smears were highly sensitive (92.1 and 93.3%, respectively) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Soybeans were grown in brown earth soil (soil pH: 6.4, organic matter: 16.17 g•kg −1 , soil moisture: 45%, and total nitrogen: 0.67 g•kg −1 ) and the average temperature of the sampled plot was 14-18 °C. Aseptic seedlings were prepared as follows: First, all seeds were surface-sterilized, and the final wash buffer was tested by the Acridine Orange Direct Count (AODC) method to ensure that no viable microbes were left [20]. Subsequently, the surface-sterilized seeds were aseptically transplanted into a germ-free potted system (diameter × height: 20 × 10 cm) that had been heat-sterilized at 121 °C for 45 min.…”
Section: Plant Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Soybeans were grown in brown earth soil (soil pH: 6.4, organic matter: 16.17 g•kg −1 , soil moisture: 45%, and total nitrogen: 0.67 g•kg −1 ) and the average temperature of the sampled plot was 14-18 °C. Aseptic seedlings were prepared as follows: First, all seeds were surface-sterilized, and the final wash buffer was tested by the Acridine Orange Direct Count (AODC) method to ensure that no viable microbes were left [20]. Subsequently, the surface-sterilized seeds were aseptically transplanted into a germ-free potted system (diameter × height: 20 × 10 cm) that had been heat-sterilized at 121 °C for 45 min.…”
Section: Plant Cultivationmentioning
confidence: 99%
“…To remove the plant-surface microorganisms, all plant samples were washed and surface sterilized immediately according to the method described by Xiao [21]. The final wash buffer was tested by AODC to confirm all samples were superficially germ-free [20]. Before the gas collection, sterilized plants were aseptically moved into a chamber unit which contained 0.5 kg of sterilized soil [22].…”
Section: Sample Preparation and Determination Of Plant Nitrite And N2mentioning
confidence: 99%
“…The acridine orange-stained smear has also been evaluated as a rapid microscopic bacteriuria screen (27,47). Hoff et al reported a sensitivity and negative predictive value of 98 and 99%, respectively, for cultures with i104 CFU/ml and suggested that the acridine orange procedure may be a cost-effective method for eliminating the need for culture of urines having <104 CFU/ml (27).…”
Section: Microscopic Methodsmentioning
confidence: 99%
“…Hoff et al reported a sensitivity and negative predictive value of 98 and 99%, respectively, for cultures with i104 CFU/ml and suggested that the acridine orange procedure may be a cost-effective method for eliminating the need for culture of urines having <104 CFU/ml (27). However, Lipsky et al found no advantage of acridine orange when compared with results from Gram-stained smears (47). They demonstrated that the diagnostic accuracy was maintained when smears were read by either an expert microbiologist or a relatively inexperienced technician.…”
Section: Microscopic Methodsmentioning
confidence: 99%
See 1 more Smart Citation